Rwanda : Poverty Reduction Strategy Paper. (IMF Staff Country Reports; Country Report ;, 2013)
This paper focuses on Economic Development and Poverty Reduction Strategy (EDPRS) 2013-2018 for Rwanda. Ownership of the EDPRS by a wide range of stakeholders at national level has been a key factor of success. The EDPRS 2 has integrated inclusiveness and sustainability as driving factors in elaborating the strategy. Community-based solutions, working closely with the population, have made possible fast-track and cost-effective implementation and increased demand for accountability, in education with the 9YBE construction of classrooms, the Crop Intensification Program in agriculture, and community-based health care programs.